2019
DOI: 10.1177/1354816619887860
|View full text |Cite
|
Sign up to set email alerts
|

Travel agent’s tour selection and sightseeing bus schedule for group package tour planning

Abstract: Two problems plague the tourism industry: (1) a scheduled group package tour (GPT) can be canceled if the number of reserved passengers does not reach a minimum number and (2) a customer’s request for a scheduled GPT will be denied once the number of reserved passengers has reached its maximum. Neither instance is desirable, because of both results in lost sales. To generate higher profit over the course of a sightseeing season, travel agent managers must schedule GPTs on suitable dates and determine the numbe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…According to Chen and Fu (2018), the metacognitive construct of CI is an individual's intellectual process which enables him/her to acquire and interpret knowledge about other cultures. Such cultural knowledge provides a better understanding of tourists' needs and perceptions easily (Triandis, 2006;You, Chen & Su, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…According to Chen and Fu (2018), the metacognitive construct of CI is an individual's intellectual process which enables him/her to acquire and interpret knowledge about other cultures. Such cultural knowledge provides a better understanding of tourists' needs and perceptions easily (Triandis, 2006;You, Chen & Su, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Complex formalities are likely to discourage tourists from choosing group package tours. Nevertheless, group tours generally include sightseeing guides, travel and accommodation packages, and catering services, which are prearranged by travel agencies (You et al, 2019). Therefore, travel agencies and tour leaders must have the necessary skills to liaison with vendors from various industries (Wong and Wang, 2009).…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Group package tours are, in general, a format of tours organized by travel agencies comprising with tour guides, transport, accommodation, and local sightseeing at an inclusive price (You et al, 2019). Chang (2020) indicated that group package tours could be formed by different agencies depending on the season and resources.…”
Section: Introductionmentioning
confidence: 99%
“…The utilization of social media data offers the possibility of personalized and dynamic tourism path planning. Data mining techniques are used in tourism path planning by analyzing tourists' comments and feedback to understand their satisfaction with specific attractions, identifying attractions in photos uploaded by users, analyzing popular attractions and hidden treasures, and analyzing popular tourist routes and trends using location data [10][11][12].…”
Section: Introductionmentioning
confidence: 99%